Vulnerability to Malnutrition in the West African Sahel - Alfani, Federica; Dabalen, Andrew; Fisker, Peter; Molini, Vasco (World Bank Group, Washington, DC, 2015)
This study estimates marginal increase in malnutrition for children ages 1-3 years from exposure to an extreme shock in the West African Sahel. The study uses knowledge of a child's birth and high resolution spatial and temporal distribution of shocks, calculated from the Normalized Difference Vegetation Index and satellite-based measures of rainfall and temperature to link a child to the shock experienced in-utero. The study finds that while around 20 percent of the children in the sample are stunted or underweight, more than 30 percent of the children in the sample are highly vulnerable to either form of malnutrition.